Sunday

August 30, 2015
Posted by **Priscilla** on Wednesday, March 21, 2012 at 1:41pm.

f(x) = sin^2 (e^sin^2 x)

I wonder if I'm right

F'(x) = 2cos(e^sin^2 x)

(sin^2 x e^sin^2 x -1)

- Calculus I -
**Steve**, Wednesday, March 21, 2012 at 2:16pmnot quite

if f = sin^2(u)

f' = 2sin(u) cos(u) u'

since u = e^v

u' = e^v v'

f = sin^2(e^sin^2 x)

f' = 2 sin(e^sin^2 x)cos(e^sin^2 x) * e^(sin^2 x) * 2 sinx cos x

= sin2x sin(2e^sin^2 x) e^(sin^2 x)

- Calculus I -
**Priscilla**, Wednesday, March 21, 2012 at 2:51pmthank you very much